Literature Review: Elements and Criteria Methodology of Enterprise Architecture for E-Government - ari cahaya puspitaningrum (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2021)
AbstractEnterprise Architecture (EA) has become a major requirement for organizations to addresses business, data, infrastructure, and information systems. EA Implementation in the government is considered very important to improve the efficiency of electronic-based services. The documentation process is challenging and is often seen as very time consuming, error-prone, and requires the collection of quality data. To create a successful, it requires to emphasize the aspects of EA development properly to prevent failure of the documentation. So, this study aims to identify the aspects of how to develop EA for e-government. The method of this study was literature review of 30 previous studies that related with the topic. Thus, this study analyzed and synthesized the studies and it can be mapped into 2 categories. The mapping consists of 1) elements and 2) criteria methodology of EA development for e-government. The findings are 23 and 11 criteria methodology of development for e-government. This study also provides some reference for further research and also provides insight into EA development for e-government that will be used by practitioners.Keywords: enterprise architecture, e-Government, e-Government EA, EA methodology AbstrakArsitektur perusahaan telah menjadi kebutuhan utama bagi organisasi untuk mengembangkan bisnis, data, infrastruktur, dan sistem informasi. Penerapan arsitektur perusahaan di pemerintahan dinilai sangat penting untuk meningkatkan efisiensi layanan berbasis elektronik. Proses dokumentasi cukup menantang dan sering kali dianggap sangat memakan waktu, rawan kesalahan, dan memerlukan pengumpulan data yang berkualitas. Untuk menciptakan kesuksesan, perlu adanya penekanan pada aspek pengembangan arsitektur perusahaan dengan baik untuk mencegah kegagalan pendokumentasian. Jadi, penelitian ini bertujuan untuk mengidentifikasi aspek bagaimana mengembangkan arsitektur perusahaan untuk e-government. Metode penelitian ini adalah studi pustaka dari 30 penelitian sebelumnya yang berhubungan dengan topik. Dengan demikian, studi ini menganalisis dan mensintesis studi tersebut dan dapat dipetakan menjadi 2 kategori. Pemetaan terdiri dari 1) elemen dan 2) metodologi kriteria pengembangan arsitektur perusahaan untuk e-government. Temuan tersebut adalah 23 dan 11 kriteria metodologi pengembangan e-government. Studi ini juga memberikan beberapa referensi untuk penelitian selanjutnya dan juga memberikan wawasan tentang pengembangan arsitektur perusahaan untuk e-government yang akan digunakan oleh para praktisi.Kata Kunci: arsitektur perusahaan, arsitektur perusahaan e-Government, e-Government, metodologi arsitektur perusahaan